Pemanfaatan Biji Kelor (Moringa Oleifera) Sebagai Koagulan Pada Pengolahan Air Payau Menjadi Air Minum Menggunakan Proses Koagulasi Ultrafiltrasi - Riny Afrima Sari; Jhon Armedi Pinem; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The availability of drinking water which complies the standard requirements of drinking water quality is getting hard to find, it makes the handling of brackish water is needed, so the kelor seed which an be used as natural coagulation is needed. Besides, the development of membrane technology nowadays grows rapidly. It can be used to process the brackish water more effective compared with conventional way. One of the used membrane technology is ultrafiltration membrane (UF). This research is done to find out of the kelor seed’s performance as coagulation and ultrafiltration membrane in processing brackish water to be good drinking water in separatig color parameter, chloride, hardness, organic essence, TDS, pH, iron, mangan, nitrate, chopper, zinc, and sulphate. This research procedure is divided into three stages which are; the first stage is bio coagulation making, the second stage is coagulation-floculation, and the third is filtration using ultrafiltration membrane. The research’s result shows the color isolation, chloride, kesadahan, organic essence, TDS, pH, iron, mangan, nitrate, chopper, zinc, and sulphate of brackish water which has been added with kelor seed’s powder effectively occurs in 350ppm and 2bar pressure can isolate 98,763%, chloride 84,303%, kesadahan 48,989%, organic essence 89,862%, TDS 44,204% pH sebesar 16,867%, iron 91,64%, mangan 89,77%, nitrate 36,58%, chopper 55, 833%, zinc 54,518% and sulphate decreasing to 82,616%, where this result has fulfilled the drinking water’s standard quality based on the rules of health ministry 2010.Keywords: Kelor seed (moringa oleifera), Brackish water, Ultrafiltration membrane.